Expression of a Chimeric Antigen Receptor in Multiple Leukocyte Lineages in Transgenic Mice. - Carmen S M Yong; Jennifer A Westwood; Jan Schröder; Anthony T Papenfuss; Bianca von Scheidt; Maria Moeller; Christel Devaud; Phillip K Darcy; Michael H Kershaw (PLoS ONE, 2015)
Genetically modified CD8+ T lymphocytes have shown significant anti-tumor effects in the adoptive immunotherapy of cancer, with recent studies highlighting a potential role for a combination of other immune subsets to enhance these results. However, limitations in present genetic modification techniques impose difficulties in our ability to fully explore the potential of various T cell subsets and assess the potential of other leukocytes armed with chimeric antigen receptors (CARs). To address this issue, we generated a transgenic mouse model using a pan-hematopoietic promoter (vav) to drive the expression of a CAR specific for a tumor antigen. Here we present a characterization of the immune cell compartment in two unique vav-CAR transgenic mice models, Founder 9 (F9) and Founder 38 (F38). We demonstrate the vav promoter is indeed capable of driving the expression of a CAR in cells from both myeloid and lymphoid lineage, however the highest level of expression was observed in T lymphocytes from F38 mice. Lymphoid organs in vav-CAR mice were smaller and had reduced cell numbers compared to the wild type (WT) controls. Furthermore, the immune composition of F9 mice differed greatly with a significant reduction in lymphocytes found in the thymus, lymph node and spleen of these mice. To gain insight into the altered immune phenotype of F9 mice, we determined the chromosomal integration site of the transgene in both mouse strains using whole genome sequencing (WGS). We demonstrated that compared to the 7 copies found in F38 mice, F9 mice harbored almost 270 copies. These novel vav-CAR models provide a ready source of CAR expressing myeloid and lymphoid cells and will aid in facilitating future experiments to delineate the role for other leukocytes for adoptive immunotherapy against cancer.